Merancang Kawasan Konservasi Perairan Berorientasi Perikanan: Studi Kasus Kawasan Konservasi Perairan Pulau Liang dan Pulau Ngali di Nusa Tenggara Barat - Aulia, Sukmaraharja; Pingkan, Jessica; Hernawati; Rafandi, Tezar; Muttaqin, Azhar; Muhidin; Retnoningtyas, Heidi (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2021)
The shape of marine protected areas (MPAs) aimed for fisheries goals should be small enough to allow for spillover of adult fished species as well as larval and juvenile fished species. Such consideration was applied during the establishment of Liang-Ngali Island MPA in West Nusa Tenggara (WNT), Indonesia, which was mainly developed to support fisheries activities around it. In WNT, biologically diverse coastal and marine ecosystems have been utilized by local residents to support their livelihoods, mainly through fisheries and tourism activities. Aside from being a home for unique habitat such as mangrove forest, seagrass beds, and coral reef, Liang and Ngali Island also shows indication of spawning aggregation sites for reef fishes such as groupers and snappers. In 2016, the government of WNT Province designated both islands as marine protected areas under the category of marine recreational park. Following the Governor Decree, a management and zonation plan of Liang-Ngali MPA was then developed by engaging stakeholders from multiple institutions. In the framework of ecosystem approach to fisheries management, the existence of MPA provides strong instrument to support the sustainability of fish resources as well as maintaining continuous livelihood for surrounding coastal communities.